Further education improves cognitive reserve and triggers improvement in selective cognitive functions in older adults: The Tasmanian Healthy Brain Project. Issue 1 (18th September 2017) - Thow, Megan E.; Summers, Mathew J.; Saunders, Nichole L.; Summers, Jeffery J.; Ritchie, Karen; Vickers, James C.
Abstract: Introduction: The strong link between early‐life education and subsequent reduced risk of dementia suggests that education in later life could enhance cognitive function and may reduce age‐related cognitive decline and protect against dementia. Methods: Episodic memory, working memory, executive function, and language processing performances were assessed annually over 4 years in 359 healthy older adults who attended university for a minimum of 12 months (intervention) and were compared against 100 healthy adult controls. Results: Multiple group latent growth curve modeling revealed a significant improvement in language processing capacity over time in the intervention group. No changes were detected for episodic memory, working memory, or executive function. Discussion: These results suggest that complex mental stimulation resulting from late‐life further education results in improved crystallized knowledge but no changes to fluid cognitive functions. Highlights: Early‐life educational attainment predicts dementia. Early‐life educational attainment predicts rate of cognitive decline. Late‐life education in healthy adults improves language processing capacity. Late‐life education enhances crystallized knowledge not fluid cognitive abilities.